Situation Report: Romania, 8 April 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Law on the Jurisdiction of People's Councils in the Field of Agriculture Law on the Use and Conservation of Water Law on Irrigation and Land Improvement Party Composition and Cadre Policy Decrees on Pardon and Amnesty Joint Enterprise for Automobile Construction to Be Created Purchase of VFW-Fokker Aircraft